Evaluación de diferentes programas de fertilización sobre la agronomía del maíz - Ruíz Cortez, Neiva Lisseth (2017)
SUMMARY The present experimental work was developed in "San Francisco", parish Febres Cordero, Babahoyo canton owned by Mr. Reinaldo Cevallos Castillo. Geographic coordinates are 790 32 'west longitude and 010 49' southern latitude. The area has tropical humid climate and the soil is flat topography and regular drainage. The Dekalb 7088 hybrid was used as seed material. The objectives were: to study the different fertilization programs on maize agronomy; Evaluate four methods for the definition of adequate fertilization programs; To measure the effects of the four fertilization programs on the development and yield of the maize crop in the wet season and to analyze the treatments economically. The treatments were constituted by the different methods of fertilization, such as fertilization according to the commercial house; Soil analysis; Apparent density of the soil and conventional (the one that the farmer uses). The experimental design used was Completely Random Block, with four treatments and five replications. The comparison of the means was developed by the Duncan test at 5% probability. During the development of the trial all agricultural practices were carried out, such as soil analysis, soil preparation, planting, weed control, irrigation, fertilization, phytosanitary control and harvesting. The evaluated data were height of insertion of the ear and of plant, diameter and length of the cob, grains by cob, weight of 1000 grains, yield and economic analysis. From the results, it was determined that the highest height of the ear of the ear was registered with the fertilization according to the apparent density of the soil, while the height of the plant stood out with the fertilization according to the soil analysis; the diameter and length of ear were influenced by fertilization according to the soil analysis, whose fertilizers helped to increase the results; the variables grain per ear and weight of 1000 grains decreased when the conventional fertilizer used by the farmers was used and the grain yield and economic analysis obtained greater results when the fertilization was carried out according to the soil analysis with net benefit of $ 474.74